2014
DOI: 10.1108/pijpsm-01-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

What clears burglary offenses? Estimating the influences of multiple perspectives of burglary clearance in Philadelphia

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 31 publications
0
25
2
Order By: Relevance
“…Conversely, in the 35 largest cities in Texas, larger Black populations increased clearance of larceny and vehicle theft but had no effect on burglary (Jang et al, 2008). Racial heterogeneity was also insignificant in a recent comparison of burglary clearance across Philadelphia neighborhoods (Lockwood, 2014).…”
Section: Community Factorsmentioning
confidence: 94%
See 4 more Smart Citations
“…Conversely, in the 35 largest cities in Texas, larger Black populations increased clearance of larceny and vehicle theft but had no effect on burglary (Jang et al, 2008). Racial heterogeneity was also insignificant in a recent comparison of burglary clearance across Philadelphia neighborhoods (Lockwood, 2014).…”
Section: Community Factorsmentioning
confidence: 94%
“…Regarding property crime, Wong (2010) found an unexpected positive relationship between residential instability (percent of the population who had moved in the last year) and a summed measure of property crime clearance in Canadian cities. In the United States, Lockwood (2014) found that neighborhood-level residential stability did not affect burglary clearance in Philadelphia, while Roth (2017) found no effect on burglary, larceny, or vehicle theft clearance across large cities.…”
Section: Community Factorsmentioning
confidence: 97%
See 3 more Smart Citations